P252 PD-1 Expression on Human Lung T Cells in Health and COPD. (19th November 2012) - McKendry, RT; Spalluto, CM; Staples, KJ; Wilkinson, TMA
Abstract : Introduction and Objectives: Patient s with chronic obstructive pulmonary disease (COPD) are susceptible to the effects of recurrent respiratory infections despite increased numbers of CD8+ T cells in the lungs. We hypothesised that the inability of CD8+ T cells to successfully combat respiratory pathogens in COPD may be due to T cell "exhaustion" - a phenomenon described in chronic infections. Exhausted CD8+ T cells have significantly reduced cytotoxicity and inflammatory cytokine release. Exhaustion is thought to be initiated by the binding of PD-1 on T cells to its ligand (PD-L1) which is expressed on epithelial cells and macrophages. PD-1 expression is upregulated in murine models of acute and chronic viral infection, but this has yet to be elucidated in human cells. We aimed to identify and quantify PD-1+ CD4+ and CD8+ T cells and cells expressing PD-L1 in the lungs of COPD patients and non-COPD controls. Methods: Lung tissue from patients undergoing surgery was digested using collagenase to form single-cell suspensions. Lung T cells were identified as populations of CD45+CD3+ cells which were either CD4+CD8- or CD4-CD8+. T cells expressing PD-1 were quantified by multi-colour flow cytometry. Patients with a FEV1/FVC ratio <70% were defined as having COPD. Results: The proportion of CD8+ T cells in the COPD lung (mean expression=40.87%, SD=14.67) was significantly higher (p=0.013, students t-test) than in non-COPD (mean expression=26.74%, SD=11.12), reflecting previous findings. PD-1 expression in CD4+ T cells appeared to be lower in COPD (mean expression=39.91%, SD=13.02) than non-COPD (mean expression=50.53%, sd=13.05) but this was not significant. PD-1 expressing CD4+ cells (mean expression=2.17%, SD=1.4) and CD8+ cells (mean expression=6.02%, sd=5.73) were detected in tissue, but not in the blood of the same patients. PD-L1 was undetectable on lung epithelial cells but was expressed on macrophages (mean expression = 2.85%, SD=1.91). Conclusion: Elements of the exhaustion pathway are expressed in the human lung in stable COPD. Further work is needed to clarify if there is an upregulation of this pathway in COPD that may explain the susceptibility of these patients to viral exacerbation. Exhaustion of cells recognising respiratory pathogens may have a significant role in COPD outcomes and requires further elucidation.